Synthesis, characterization, and catalytic activity in Suzuki coupling and catalase-like reactions of new chitosan supported Pd catalyst. (10th July 2016) - Baran, Talat; Inanan, Tülden; Menteş, Ayfer
Graphical abstract: Highlights: Catalase-like activity of biomaterial supported Pd catalyst decreased by only 12.9% at the end of 10 cycle. Synthesis of biarlys using free solvent at 4 min under MW was succeeded. TON and TOF values for both applications determined high. Suzuki reaction exhibited high selectivity and no homo-coupling by-products. Abstract: The aim of this study is to analyze the synthesis of a new chitosan supported Pd catalyst and examination of its catalytic activity in: 1. Suzuki coupling reactions by improving a simple, fast, and solvent-free microwave method. 2. H2 O2 decomposition reaction to find out its redox potential. Pd catalyst was synthesized using chitosan as a biomaterial and characterized with FTIR, TG/DTG, XRD, 1 H NMR, 13 C NMR, SEM-EDAX, ICP-OES, Uv–vis spectroscopies, and magnetic moment, along with molar conductivity analysis. Biomaterial supported Pd catalyst indicated high activity and long life time as well as excellent turnover number (TON) and turnover frequency (TOF) values in Suzuki reaction. Biomaterial supported Pd catalyst catalyzed H2 O2 decomposition reaction with considerable high activity using comparatively small loading catalyst (10 mg). Redox potential of biomaterial supported Pd catalyst was still high without negligible loss (13% decrease) after 10 cycles in reusability tests. As a consequence, eco-friendly biomaterial supported Pd catalyst has superior properties such as high thermal stability, long life time, easy removal from reaction mixture and durability to air, moisture and high temperature.